A study on the confidence level of international halal labelled products among Muslim consumers / Muhamad Radzi Rosly - Rosly, Muhamad Radzi (2013)
The objective of this research is to study the confidence level of International Halal labelled products among Muslim consumers in Malaysia. Researcher’s respondents came from government servants at Putrajaya who is Malay Muslim consumers as the sample. The respondents will also grouped under four categories of sectors namely, professional, services, students and others.